PENGARUH UPAH MINIMUM TERHADAP PENGURANGAN TINGKAT PENGANGGURAN TERBUKA DI INDONESIA - Rully Sutansyah Effendy (STIE Pelita Nusantara Semarang, 2019)
Improper management of population will cause population problems, especially in the field of employment. Existing jobs have not been able to meet the needs of the work resulting in unemployment problems. The number of unemployed people in Indonesia reaches 7 million from the workforce.The purpose of this study was to determine the effect of economic growth, worker minimum wages, and inflation on unemployment in Indonesia. The analysis technique used is multiple linear regression, using sequential data time during 2003-2018.The results of this study found that inflation, economic growth, and minimum wages of workers have a strong influence on the level of open unemployment. The results of multiple linear regression show the minimum wage as a variable that has a very large effect on the decline in the unemployment rate. Variable economic growth affects the level of open unemployment. Positive inflation affects the level of open unemployment.